Pengaruh Luas Bukaan Terhadap Kebutuhan Pertukaran Udara Bersih Dalam Rumah Tinggal - sukawi, sukawi; Hardiman, Gagoek (architecture department, Engineering faculty, Universitas Diponegoro, 2014)
Humid tropic climate conditions is not entirely in according with human needs in order to need the physical comfort. The solar radiation is high, people tropic to avoid the tropical sun directly because it can cause thermal discomfort. In the building are also trying to avoid breaking of solar radiation by direct sunlight to heat from the radiation does not cause heat to buildings. A very important factor for the convenience of a room is the existence of cross ventilation. In the humid tropics, the best orientation is a position that allows for cross ventilation as long as possible. Rare good building orientation to the sun as well as both the main wind direction. Character home in humid tropical areas are generally open so it can serve to capture and stream winds. According Boutet (1987) the amount of air flow is happening in the room depending on the area of the opening hole, the wind direction and wind speed. Airflow velocity becomes greater when the hole in the air (inlet) is smaller than the hole exit (outlet). Cross ventilation can be achieved if there is a hole in (inlet) and exit hole (outlet). Dimensions of the window opening is 20% x large wall sufficient minimum requirements. Of the 7 houses on stilts in the study all have large openings that need the minimum requirements for the air exchangeÂ in the house. This is to support the creation of indoor thermal comfort.